A Multi-Grid Algorithm for Stokes Problem (Journal of Computational Mathematics, 2021)
In this paper we describe a multi-grid algorithm for the penalty procedure of Stokes problem. It is proved that the convergence rate of the algorithm is bounded away from 1 independently of the meshsize. For convenience, we only discuss Jacobi relaxation as smoothing operator in detail.